2013
DOI: 10.1007/s00280-013-2181-2
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 predicts outcome in patients with gastric cancer treated with adjuvant cisplatin-based chemotherapy

Abstract: Excision repair cross-complementing gene 1 by IHC might predict patients more likely to benefit from adjuvant cisplatin-based chemotherapy in curatively resected gastric cancer. In patients exhibiting ERCC1 positive tumors, alternative regimens should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 36 publications
3
30
0
1
Order By: Relevance
“…In patients with surgically resected NSCLC who do not receive adjuvant chemotherapy, those with high ERCC1 expression experience longer survival than patients with low ERCC1 expression [133] Preclinical data evaluating the predictive and prognostic value of ERCC1 in GC has revealed mixed results. Similar to in NSCLC, ERCC1 has been found to be a negative predictive factor in a European population receiving adjuvant cisplatin-based chemotherapy after gastrectomy because ERCC1 negativity was associated with longer OS [134]. Similar results were seen in an Asian population that received adjuvant oxaliplatinbased chemotherapy [135].…”
Section: Potential New Targetssupporting
confidence: 71%
“…In patients with surgically resected NSCLC who do not receive adjuvant chemotherapy, those with high ERCC1 expression experience longer survival than patients with low ERCC1 expression [133] Preclinical data evaluating the predictive and prognostic value of ERCC1 in GC has revealed mixed results. Similar to in NSCLC, ERCC1 has been found to be a negative predictive factor in a European population receiving adjuvant cisplatin-based chemotherapy after gastrectomy because ERCC1 negativity was associated with longer OS [134]. Similar results were seen in an Asian population that received adjuvant oxaliplatinbased chemotherapy [135].…”
Section: Potential New Targetssupporting
confidence: 71%
“…Significantly longer OS (P = 0.04) was found in patients categorized as ERCC1 negative by immunohistochemistry. Thus, ERCC1 may help in predicting which patients are more likely to benefit from adjuvant cisplatin-based chemotherapy in curatively resected gastric cancer (De Dosso et al, 2013). In a study from China, the effects of ERCC1 expression on survival in were evaluated in 57 gastric cancer patients treated with surgery followed by oxaliplatin-based adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…High tumoral expression of ERCC1 was associated with decreased OS in patients who received platinum-based adjuvant chemotherapy (16.7 months vs 53.8 months; P = 0.03) (Squires et al, 2013). In the investigation by De Dosso et al (2013), the expression of ERCC1 expression in tumor samples obtained from surgical specimens of 68 patients treated with adjuvant cisplatin-based chemotherapy for gastric cancer were analyzed by immunohistochemistry. Significantly longer OS (P = 0.04) was found in patients categorized as ERCC1 negative by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Excision repair cross-complementation group 1 (ERCC1) is an endonuclease essential in the nucleotide excision repair pathway and plays a role in DNA repair capacity and cancer risk as well as the clinical outcome of cancer (Wang et al, 2005). Recently, several studies suggested that variants in ERCC1 influence the susceptibility to and prognosis of various cancers Mlak et al, 2013;Yang et al, 2013;De Dosso et al, 2013). Few studies have investigated the role of ERCC1 variants in the clinical outcome in NSCLC (Ozdemir et al, 2013;Mlak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%